On The Issue Of Management Of State And Non-State General Education Institutions - Gasparyan, Mkhitar (Զանգակ հրատ.)
This study explores the management peculiarities of state and non-state general education institutions, emphasizing teacher engagement, public demand, and the evolution of management mechanisms. Based on statistical data from 2010 to 2023 in the Republic of Armenia, a comparative analysis was conducted to reveal the development dynamics of both sectors. The findings indicate that while the state sector maintains a higher level of teacher involvement, non-state institutions exhibit greater flexibility and innovation in their management approaches. Special attention is given to the role of teachers’ educational backgrounds and qualifications in shaping management strategies. The study also highlights key differences in teacher engagement across primary, secondary, gymnasium, and high school programs, supported by correlation analysis. Moreover, risks associated with management practices in non-state institutions, such as rigid administrative structures and employment instability, are discussed. The research underscores the necessity of integrating effective private sector innovations into the state education management system. It concludes with practical recommendations aimed at improving governance models, enhancing educational quality, and better addressing societal demands. By focusing on teacher engagement indicators and public expectations, the study contributes to a deeper understanding of how effective management strategies can foster the sustainable development of the general education sector.
Keywords: Education